Flipped Classroom in Teaching Writing at SMP Muhammadiyah Parepare - Agustiari, Tania Astri; Salasiah, Salasiah; Sudarmanto, Sudarmanto (La Parole : Journal of Language Teaching and Pedagogy, 2023)
Writing is one of the English language competencies that, in addition to other skills, must be taught. According to the government's recommended curriculum, junior high school students must study a number of texts. Descriptive text is one of them. A descriptive text is a piece of writing that describes something, someone, or a situation. Most of the students have difficulty with it. They are confused about what to write, despite the fact that they are familiar with the subject. As a result, the researcher tried to use the reverse classroom strategy in this research. The researcher applied a pre-experimental method with two groups, namely, pre-test and post-test. The researcher applies the flipped classroom strategy in presenting the material. The population in this research were seventh grade students at SMP Muhammadiyah parepare in the 2021/2022 academic year. The sample in this research was taken using purposive sampling, consisting of 18 students from one class, taken from the seventh grade student population of SMP Muhammadiyah Parepare as an experimental class. The results of the data analysis showed that the students writing abilities increased, but not significantly. The results of the pre-test got an average score of 45,55% while the post-test got an average score of 79,94%. It means that, teaching writing through the flipped classroom can help some students with their writing texts. In addition, the average post-test score of 79,94 is higher than the minimu criteria at SMP Muhammadiyah Parepare, which is 70. While analyzing the data using the t-test formula, the results show that the test value (0,2144) is lower than the t-table ((α = 0.05: 1.739). This means that the null hypothesis (H0) is accepted and the alternative hypothesis (H1) is rejected. The research concluded that teaching writing through the flipped classroom was able to improve students wr.iting abilities, but not significantly.